Interleukin 33 Selectively Augments Rhinovirus-Induced Type 2 Immune Responses in Asthmatic but not Healthy People - Jurak, Lisa M.; Xi, Yang; Landgraf, Megan; Carroll, Melanie L.; Murray, Liisa; Upham, John W. (Frontiers in Immunology, 2018)
Interleukin 33 (IL-33) is an epithelial derived cytokine that initiates type 2 immune responses to allergens, though whether IL-33 has the ability to modify responses to respiratory viral infections remains unclear. This study aimed to investigate the effects of IL-33 on rhinovirus (RV) induced immune responses by circulating leukocytes from people with allergic asthma, and how this response may differ from non-allergic controls. Our experimental approach involved co-exposing peripheral blood mononuclear cells (PBMC) to IL-33 and RV in order to model how the functions of virus responsive lymphocytes could be modified after recruitment to an airway environment enriched in IL-33. In the current study, IL-33 enhanced RV-induced IL-5 and IL-13 release by cells from people with allergic asthma, but had no effect on IL-5 and IL-13 production by cells from healthy donors. In asthmatic individuals, IL-33 also enhanced mRNA and surface protein expression of ST2 (the IL-33 receptor IL1RL1) while soluble ST2 concentrations were low. In contrast, IL-33 had no effect on mRNA and surface expression of ST2 in healthy individuals. In people with allergic asthma, RV-activated ST2+ innate lymphoid cells (ST2+ILC) were the predominant source of IL-33 augmented IL-13 release. In contrast, RV-activated natural killer cells (NK cells) were the predominant source of IL-33 augmented IFNγ release in healthy individuals. This suggests that the effects of IL-33 on the cellular immune response to RV differ between asthmatic and healthy individuals. These findings provide a mechanism by which RV infections and IL-33 might interact in asthmatic individuals to exacerbate type 2 immune responses and allergic airway inflammation.